The Influence of Internet financial Reporting on The Market Value of Case Study Companies on LQ45 Companies Listed on The Indonesia Stock Exchange - Dian Annisa Putri (Proceedings International Conference on Sustainable Innovation (ICoSI), 2021)
The problem in this research is the advancement of technology to make the company that makes official website in disclosing financial and nonfinancial information, Internet change the presentation of company information. This research aims to determine the influence of Internet Financial Reporting practices on the market value of LQ45 decisively company listed on the Indonesia Stock Exchange (IDX) period 2018. The population of this research is 50 LQ45 companies listed on the Indonesia Stock Exchange (IDX) period 2020. The sampling method used is purposive sampling, with a sample number of 32 companies. The data analysis technique in this study is a double linear regression analysis. An independent variable is internet financial reporting. The research uses control variables i.e. company size, profitability, and liquidity. The dependent variables in this study are the company's market value. The conclusion in this study is that internet financial reporting practices have a significant effect on the company's market value. Variable control company size, liquidity, and profitability have a significant effect on the company's market value. The advice in this research is that the Indonesian Institute of Accountants (IAI) should issue financial accounting standards themed on Internet Financial Reporting. Because the disclosure of financial and non-financial information through the Internet called Internet Financial Reporting is still mandatory disclosure or voluntary disclosure. So that each company can make website-based disclosures in accordance with the standards officially enforced by the Indonesian Institute of Accountants (IAI).